Catalyst-free three-component synthesis of highly functionalized 2, 3-dihydropyrroles. Issue 12 (23rd May 2018) - Wang, Dong; Li, Linna; Feng, Hairong; Sun, Hua; Almeida-Veloso, Fabrice; Charavin, Marine; Yu, Peng; Désaubry, Laurent
Abstract : An efficient catalyst-free synthesis of fully substituted 2, 3-dihydropyrroles has been achieved in one step through the three-component reaction of amines, aromatic aldehydes and α-ketoamides. Abstract : An efficient synthesis of fully substituted 2, 3-dihydropyrroles has been achieved in one step through the three-component reaction of amines, aromatic aldehydes and α-ketoamides. This atom-economical and catalyst-free reaction is highly stereoselective and generates underexplored heterocycles in a single step. These compounds were examined in an enzymatic assay that led to the identification of potent α-glucosidase inhibitors, thereby demonstrating the utility of this novel methodology in medicinal chemistry.